Analysis of the Influence of Groundwater Level Fluctuation on Karst Soil Cave Collapse - Xuejun Chen; Mingming Xue; Yu Song (Geofluids)
Artificial water pumping and rainfall will induce groundwater level fluctuations, leading to large-scale karst collapse. Therefore, the combination of physical model test and FLAC3D numerical simulation is adopted to simulate the soil cave collapse caused by three different initial water level fluctuations in this paper. The influence of various initial water level heights on the variation of water-gas pressure, soil pressure of the overlying soil layer, and deformation in the existing soil cave during the fluctuation was analyzed. The relationship between initial water level height, deformation and collapse of the cave, and water-gas pressure was established, and the action law of water level fluctuations on the collapse of soil cave was introduced. The results show the following: (1) The change of water-gas pressure positively correlates with the initial water level height, directly affecting the overlying soil layer deformation. (2) The change of soil pressure of overlying soil positively correlates with the change of water-gas pressure under different initial water level fluctuations. (3) The deformation and collapse difficulty of the soil cave negatively correlates with the initial water level. The higher the initial water level, the stronger the negative pressure absorption and positive pressure gas explosion effect on the overburden on the soil cave and the collapse will occur with fewer water level fluctuations. (4) The numerical simulation results are consistent with the laboratory model test. These laws elucidate the change of water-gas pressure in different initial water level fluctuations and reveal the collapse mechanism of water level fluctuations. It will provide essential theoretical support for further research on the action law of hydrodynamic factors on karst collapse and a scientific and reasonable basis for urban groundwater pumping control, karst and roadbed collapse prevention and prediction.